2022
DOI: 10.3389/fcvm.2022.883873
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a HeartLogicTM Based Care Path in the Management of a Real-World Chronic Heart Failure Population

Abstract: AimEarly detection of impending fluid retention and timely adjustment of (medical) therapy can prevent heart failure related hospitalizations. The multisensory cardiac implantable electronic device (CIED) based algorithm HeartLogicTM aims to alert in case of impending fluid retention. The aim of the current analysis is to evaluate the performance of the HeartLogicTM guided heart failure care path in a real-world heart failure population and to investigate whether the height of the index and the duration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…These findings may have implications for the strategies for patient enrolment in RM programs, where current RM systems are mainly targeted at early detection of heart failure exacerbation. 22 , 23 Prospective trials including patients regardless of ICD indications are required to confirm these findings. Moreover, the IN-TIME trial demonstrated heart failure patients with a history of atrial fibrillation (AF) to be more likely to benefit from RM than were patients without a history of AF.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may have implications for the strategies for patient enrolment in RM programs, where current RM systems are mainly targeted at early detection of heart failure exacerbation. 22 , 23 Prospective trials including patients regardless of ICD indications are required to confirm these findings. Moreover, the IN-TIME trial demonstrated heart failure patients with a history of atrial fibrillation (AF) to be more likely to benefit from RM than were patients without a history of AF.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, in addition to the use of LUS, pro-BNP and clinical evaluation, a multisensory cardiac implantable electronic device (CIED)-based algorithm, HeartLogicTM, was created to alert in case of impending fluid retention. Felten et al demonstrated through this method that higher and persistent alerts are indicative for true positive alerts and higher index values are indicative for more severe fluid retention [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…69 Feijen et al reported on the integration of the HeartLogic with an HF care pathway using telephone-based clinical assessments (107 participants, 136 alerts over a median 14-month study period). 6 Alerts were true positives in 71% of cases, with a sensitivity and specificity of 0.79 (95% CI [0.68-0.86]) and 0.88 (95% CI [0.08-0.15]), respectively. 6 The MANAGE-HF randomised trial comparing HeartLogic 'on' versus 'off' is ongoing and due to complete in 2025 (NCT03237858).…”
Section: Boston Scientific Heartlogic Indexmentioning
confidence: 99%
“…6 Alerts were true positives in 71% of cases, with a sensitivity and specificity of 0.79 (95% CI [0.68-0.86]) and 0.88 (95% CI [0.08-0.15]), respectively. 6 The MANAGE-HF randomised trial comparing HeartLogic 'on' versus 'off' is ongoing and due to complete in 2025 (NCT03237858).…”
Section: Boston Scientific Heartlogic Indexmentioning
confidence: 99%
See 1 more Smart Citation